Pengenalan dan Pencegahan Ransomware dalam Dunia Penerbangan: Penguatan Literasi Siber bagi Siswa SMK Dirgantara Putra Bangsa - Albanna, Faiz; Ristiani, Ristiani; Ginusti, Gallis Nawang; Karnaen, Irfan Abdulhafizh; Purnama, Yunus; Meilani, Irwina; Maulana, Adipura Danang; Syaputra, Andi (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The growing integration of digital technology in various sectors, including aviation, has significantly increased vulnerability to cyber threats such as ransomware. This community service activity aimed to raise awareness and improve students’ understanding of ransomware threats and prevention strategies in the aviation industry. The target participants were 24 tenth-grade students from SMK Dirgantara Putra Bangsa in Sleman, Yogyakarta. The method used was an offline interactive seminar, consisting of a lecture, discussion, and digital-based evaluation through pre-test and post-test questionnaires. The program was implemented in four phases: planning, preparation, implementation, and evaluation. The session was delivered by a professional speaker from Rumahweb, one of Indonesia’s largest hosting companies. Results showed a significant improvement in student knowledge, with average scores increasing from 15.29 (pre-test) to 21.38 (post-test). Statistical analysis confirmed a strong positive correlation (r = 0.731, p < 0.05) and a significant mean difference (p = 0.000), indicating the effectiveness of the activity. Additionally, the event was documented and published via YouTube and Harian Jogja, expanding its public impact. This initiative demonstrated the importance of digital literacy and collaborative efforts between higher education, professionals, and vocational schools in strengthening national cybersecurity awareness.